Intermittent Theta Burst Stimulation of the Prefrontal Cortex in Cocaine Use Disorder: A Pilot Study - Sanna, Angela; Fattore, Liana; Badas, Paola; Corona, Giorgio; Cocco, Viola; Diana, Marco (Frontiers in Neuroscience, 2019)
Transcranial Magnetic Stimulation (TMS) is earning a role in the therapeutic arsenal of cocaine use disorder. A widespread and still growing number of studies have reported beneficial use of repeated TMS (rTMS) in reduction of craving, intake and cue-induced craving in cocaine addicts. In spite of these encouraging findings, many issues are still unresolved such as brain area to be stimulated, laterality of the effects, coil geometry and stimulation protocols/parameters. Intermittent theta burst stimulation (iTBS) is a more tolerable protocol administered at lower intensities and shorter intervals than conventional repeated TMS (rTMS) protocols. Yet, its effects on cocaine craving and length of abstinence in comparison with standard high frequency (10-15Hz) protocols have never been evaluated so far. In the present paper we describe the effect of the bilateral iTBS of the prefrontal cortex (PFC) in a population (n=25) of treatment-seeking cocaine addicts, in an outpatient setting, and compare them with 15 Hz stimulation of the same brain area (n=22). The results indicate that iTBS produces effects on cocaine consumption and cocaine craving virtually superimposable to the 15 Hz rTMS group. Both treatments had low numbers of dropouts and similar side-effects, safety and tolerability profiles. While larger studies are warranted to confirm these observations, iTBS appears to be a valid approach to be considered in treatment-seeking cocaine addicts, especially in light of its brief duration (3 mins) vs 15 Hz stimulation (15 mins). The use of iTBS would allow increasing the number of patients treated per day with current rTMS devices, thus reducing patient discomfort and hopefully reducing drop-out rates without compromising clinical effectiveness.